Designing a Positive Psychological Self-Care Educational Package for Male Adolescents with High-Risk Behaviors - Khakrand, Mohsen; Ghanbari Panah, Afsaneh; Sadeghi Afjeh, Zohreh; Niknam, Mandana (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to design and validate a positive psychological self-care educational package for male adolescents with high-risk behaviors. Methods and Materials: This study was conducted using a qualitative applied research design based on grounded theory and thematic analysis. The study population included psychologists with direct professional experience working with adolescents with high-risk behaviors, theoretical and empirical literature related to positive psychology and psychological self-care, and university experts in psychology. Twenty-two psychologists working in counseling centers affiliated with the Department of Education in Tehran were selected through purposive sampling and participated in semi-structured interviews until theoretical saturation was achieved. In addition, domestic and international scientific sources related to positive psychology, self-care, emotion regulation, coping self-efficacy, and adolescent high-risk behaviors were reviewed and analyzed. Data collection tools included semi-structured interviews, a researcher-made content validity form, and an inter-rater agreement form. Data were analyzed through open, axial, and selective coding. After the educational package was developed, six faculty experts evaluated its content validity and overall quality. Findings: The qualitative analysis resulted in the extraction of 60 initial codes, which were organized into 12 main categories, including communication establishment, emotion recognition, recognition of strengths, optimism, stress management, anger management, social skills, empathy, gratitude, meaning in life, spirituality, and resilience. These categories formed the conceptual and structural foundation of the final 12-session positive psychological self-care educational package. The package integrated emotional, cognitive, interpersonal, and resilience-oriented components designed to improve adolescents’ psychological self-care capacities and coping resources. Content validity analysis showed that all extracted components achieved acceptable content validity ratios and were confirmed as essential by the expert panel. The inter-rater agreement coefficient also demonstrated a high level of expert consensus regarding the appropriateness, coherence, and applicability of the package. Conclusion: The findings suggest that positive psychological self-care for male adolescents with high-risk behaviors should be conceptualized as a multidimensional process integrating emotional regulation, adaptive coping, interpersonal competence, optimism, meaning, spirituality, and resilience.